Blocked early-stage latency in the peripheral blood cells of certain individuals infected with human immunodeficiency virus type 1. - Seshamma, T (1992)
Human immunodeficiency virus type 1 (HIV-1) infections of humans have a natural history characterized by a variable but usually slow progression to an immunodeficient state. We have described a molecular model of HIV-1 proviral latency in certain cell lines, characterized by extremely low or undetectable levels of unspliced genomic HIV-1-specific RNA but significant levels of multiply spliced HIV-1-specific RNA. We have utilized a quantitative reverse transcriptase-initiated polymerase chain reaction to measure the levels of various HIV-1 RNA species in peripheral blood mononuclear cells. The median level of multiply spliced HIV-1 RNA was dramatically higher than the median level of unspliced viral RNA in asymptomatic individuals. In addition, HIV-1 RNA patterns characterized by at least a 10-fold excess of multiply spliced to unspliced viral RNA were significantly more common in asymptomatic individuals than in patients with the acquired immunodeficiency syndrome. We suggest that asymptomatic clinical HIV-1 infection is characterized by a preponderance of HIV-1-infected peripheral blood cells blocked at an early stage of HIV-1 infection. This viral expression pattern, which we have called blocked early-stage latency, may constitute a reservoir of latently infected cells in certain HIV-1-infected persons.